Подождите немного. Документ загружается.
H =
1
2
m( ˙r
2
+ r
2
˙ϕ
2
) + U(r, ϕ) =
p
2
r
2m
+
p
2
ϕ
2mr
2
+ U(r, ϕ).
∂H
∂p
r
=
p
r
m
,
∂H
∂p
ϕ
=
p
ϕ
mr
2
,
∂H
∂r
= −
2p
2
ϕ
mr
3
+
∂U
∂r
,
∂H
∂ϕ
=
∂U
∂ϕ
.
˙r =
p
r
m
, ˙ϕ =
p
ϕ
mr
2
, ˙p
r
=
2p
2
ϕ
mr
3
−
∂U
∂r
, ˙p
ϕ
= −
∂U
∂ϕ
.
2s
2s q
i
(t) p
i
(t)
q
i
(t) p
i
(t)
t
o
p
i
(t
o
) q
i
(t
o
)
f(q
i
, p
i
, t)
df
dt
=
∂f
∂t
+
X
i
(
∂f
∂q
i
˙q
i
+
∂f
∂p
i
˙p
i
).
df
dt
=
∂f
∂t
+
X
i
(
∂f
∂q
i
∂H
∂p
i
−
∂f
∂p
i
∂H
∂q
i
).
H f
(H, f) =
X
i
(
∂H
∂p
i
∂f
∂q
i
−
∂H
∂q
i
∂f
∂p
i
).
f(q
i
, p
i
, t)
df
dt
=
∂f
∂t
+ (H, f).
q
i
∂q
i
∂t
= 0, (H, q
i
) =
∂H
∂p
i
, ˙q
i
=
∂H
∂p
i
.
f p
i
H
q
i
Q
i
q
i
= f
i
(Q
i
, t).
q
i
p
i
q
i
= f
i
(Q
i
, P
i
, t), p
i
= F
i
(Q
i
, P
i
, t)
Q
i
P
i
Q
i
P
i
˙
Q
i
=
∂H
0
∂P
i
,
˙
P
i
= −
∂H
0
∂Q
i
,
H
0
S
0
=
Z
t
2
t
1
X
i
P
i
dQ
i
− H
0
dt.
S S
0
X
i
p
i
dq
i
− H dt −
X
i
P
i
dQ
i
+ H
0
dt = dF (q
i
, Q
i
, t).
p
i
=
∂F
∂q
i
, P
i
= −
∂F
∂Q
i
, H
0
− H =
∂F
∂t
.
2s
H
0
F (Q
i
, q
i
, t)
H =
p
2
2m
+
mω
2
q
2
2
.
F (q, Q, t) = 0.5 mωq
2
Q
q =
v
u
u
u
t
2P
mω
sin Q, p =
√
2mωP cos Q, H
0
= H = ωP.
˙
Q =
∂H
0
∂P
= ω,
˙
P = −
∂H
0
∂Q
= 0.
Q = ωt + C
1
P = C
2
q p
H
0
Q
i
= A
i
= , P
i
= B
i
= .
q
i
p
i
A
i
B
i
S
F S
p
i
=
∂S(q
i
, A
i
, t)
∂q
i
, B
i
= −
∂S(q
i
, A
i
, t)
∂A
i
,
0 =
∂S(q
i
, A
i
, t)
∂t
+ H(q
i
, p
i
, t).
S
S
S
A
i
∂S
∂t
+ H(q
i
,
∂S
∂q
i
, t) = 0.
s
s + 1
s + 1
S s
s
s